Pengaruh Thought Stopping Terhadap Penurunan Tingkat Kecemasan Masyarakat Penerima Vaksinasi Covid-19 di Wilayah Kerja Puskesmas Terminal Banjarmasin: The Effect of Thought Stopping on Reducing Axiety Levels for the Recipient of the Covid-19 Vaccination in the Banjarmasin Terminal Health Center Work Area - Tya Ayu Widyasari; Subhannur Rahman; Desilestia Dwi Salmarini (Jurnal Surya Medika (JSM), 2023)
The COVID-19 pandemic has caused various impacts that have been experienced by Indonesian people. The government has provided a breakthrough to reduce the number of Covid-19 in Indonesia, namely the Covid-19 vaccination. The hope of the Covid-19 vaccination is to create herd immunity for the people of Indonesia, but there are still many people who experience anxiety during the process of receiving the Covid-19 vaccination. A preliminary study conducted in the working area of ​​the Banjarmasin Terminal Health Center showed that 5 out of 10 people experienced anxiety. The anxiety experienced by the community can be reduced in various ways, one of which is the provision of thought stopping therapy interventions. This study aims to determine whether there is an effect of thought stopping on reducing the anxiety level of the people who receive the COVID-19 vaccination in the working area of ​​the Banjarmasin Terminal Health Center.This research uses quantitative methods. The population taken is the community receiving the covid-19 vaccination in the working area of ​​the Banjarmasin Terminal Health Center. The number of samples is 30 people with purposive sampling technique. The results of the Paired T-Test statistic test showed that the significance value (2-tailed) was 0.000 <0.05, indicating a difference between anxiety before and after the intervention. There is an effect of thought stopping on reducing the level of anxiety of the people receiving the covid-19 vaccination in the working area of ​​the Banjarmasin Terminal Health Center